THE EFFECTIVENESS OF BARIATRIC AND METABOLIC SURGERY IN THE TREATMENT OF OBESITY - Teshaev, O.R.; Ruziev, U.S.; Murodov, A.S.; Zhumaev, N.A. (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
To evaluate the effectiveness of bariatric and metabolic surgery in the treatment of patients with various forms of obesity. Material and methods: By us at the Department of Surgical Diseases TMA on the basis of the 1st city clinical hospital in Tashkent in the period 2015-2019. 40 patients aged 22-62 years with various forms of obesity and related metabolic disorders were operated on. Body mass index ranged from 28-62. All patients had symptoms of metabolic disturbances of one degree or another. Results: Patients underwent sleeve resection of the stomach, laparoscopic mini-gastric bypass, gastric bypass (Roux en Y gastric bypass) with 180 cm shunt and 70 cm alimentary loop as an independent method for the surgical treatment of type 2 diabetes associated with obesity. The efficiency of weight loss after drainage of the gastric resection was 73%, after shunt operations 89%. Gastro-bypass surgery has been shown to be effective even in patients with type 2 diabetes mellitus with a body mass index of up to 30. Conclusions: Gastro-bypass surgery is the gold standard in the surgical treatment of obesity and its associated diseases. The use of minimally invasive gastric bypass methods contributes to a sharp decrease in the number of general surgical and specific complications.